Peradaban Islam pada Masa Khalifah Abu Bakar Ash-Shiddiq - Tasya Aryati Sakinah; Wafiq Zahira Mardatilah; Sania Junila (BADAN PENERBIT STIEPARI PRESS, 2025)
Islamic civilization during the time of Abu Bakar As-Siddiq was a period that played a key role in the early development of Islam. Abu Bakr, who was the closest friend of the Prophet Muhammad SAW, was the first Caliph of Muslims after the death of the Prophet. This journal explains Abu's role Burn in building Islamic civilization, which includes the spread of religion, collecting the Koran, financial and social policies, as well as an emphasis on justice and law. His leadership wisdom and the Islamic principles he implemented have helped form the basis for strong and sustainable Islamic civilization. This period plays an important role in determine the future of Islam and provides inspiration for the next generation to live a life in accordance with the noble values ​​of Islam.